2021
DOI: 10.3390/sym13010084
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Video Steganography-Based Botnet Communication Model in Telegram SNS Messenger

Abstract: In botnets, a bot master regularly sends command and control messages (C & C messages) to bots for various purposes, such as ordering its commands to bots and collecting critical data from bots. Although such C & C messages can be encrypted by cryptographic methods to hide them, existing botnet detection mechanisms could detect the existence of botnets by capturing suspicious network traffics between the bot master (or the C & C server) and numerous bots. Recently, steganography-based botnets (steg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The purpose of steganography is to secretly convey messages that others do not notice on the cover stream. This deceptive method prevents a security system from noticing whether the stream is an important message [16,17]. The initial compressed video steganography research began with a video watermarking method that manipulates the lower bits of the brightness value in the raw video domain, rather than in the compressed domain, to make it visually indistinguishable.…”
Section: Compressed Video Steganography Methodsmentioning
confidence: 99%
“…The purpose of steganography is to secretly convey messages that others do not notice on the cover stream. This deceptive method prevents a security system from noticing whether the stream is an important message [16,17]. The initial compressed video steganography research began with a video watermarking method that manipulates the lower bits of the brightness value in the raw video domain, rather than in the compressed domain, to make it visually indistinguishable.…”
Section: Compressed Video Steganography Methodsmentioning
confidence: 99%
“…When considering such late attacks, it was found that many checks on different AI calculations of the CICIDS2017 datasets were not sufficient for port checks and DDoS attacks. Kwak et al [16], proposed a video steganography botnet model. In addition, they plan to use another video steganography technology based on the payload method (DECM: Frequency Division Embedded Component Method), which can use two open devices VirtualDub and Stegano to implant significantly more privileges than existing tools information.…”
Section: Related Workmentioning
confidence: 99%
“…Computer steganography -hiding data or messages in objects of the program structure of a computer or computer network (in computer programs, in protocols, in sectors of disk space, etc.) [29][30][31][32].…”
Section: Technologies Of Stego-embeddingmentioning
confidence: 99%